2019
DOI: 10.17129/botsci.2200
|View full text |Cite
|
Sign up to set email alerts
|

Nodule-forming Sinorhizobium and arbuscular mycorrhizal fungi (AMF) improve the growth of Acacia farnesiana (Fabaceae): an alternative for the reforestation of the Cerro de la Estrella, Mexico

Abstract: Background: Cerro de la Estrella (CE) is a natural reserve in Mexico City that suffers from afforestation, and its restoration with Acacia farnesiana is being considered.Question: Will the nodule-forming rhizobia and arbuscular mycorrhizal fungi (AMF) associated with the CE soil support A. farnesiana growth?Study species: Acacia farnesiana (L.) Willd. (Fabaceae).Methods: Mycorrhizal fungi, nodule-forming rhizobia and physicochemical characteristics of the CE soil were studied to determine if they are suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, it has been shown that the most surprising results from the inoculation of PGPB are presented when utilizing soils with nutritional deficiencies, poor irrigation and adverse weather conditions (Grover et al 2013, Inostroza et al 2017. In our case, the soil that was utilized contained serious nutritional deficiencies in organic matter, nitrogen and soluble phosphorus, which were previously determined (Gómez-Acata et al 2019). Therefore, with the results obtained, we corroborate the importance of the inoculation with Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, it has been shown that the most surprising results from the inoculation of PGPB are presented when utilizing soils with nutritional deficiencies, poor irrigation and adverse weather conditions (Grover et al 2013, Inostroza et al 2017. In our case, the soil that was utilized contained serious nutritional deficiencies in organic matter, nitrogen and soluble phosphorus, which were previously determined (Gómez-Acata et al 2019). Therefore, with the results obtained, we corroborate the importance of the inoculation with Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 88%
“…The sand and soil were mixed in a ratio of 2:5 volume/volume. The soil is considered as a low-nutrient soil due to the organic matter (4.46 %), nitrogen content (0.13 %) and soluble phosphorus (1.7 % mg Kg -1 ) as determined previously (Gómez-Acata et al 2019). Two control groups without bacterial inoculation were included, one was irrigated only with water and the other watered with HNS.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%